Colon Cancer Genetic and Epigenetic Changes, Etiopathogenesis, Risk Factors, Treatment: Literature Review - Ūbaitė, Gabrielė; Remeikaitė, Aurelija; Žilinskas, Justas (Lietuvos chirurgija, 2024)
Background. Colorectal cancer (CRC) ranks as the third leading cause of cancerrelated mortality worldwide. Recent years have witnessed an increase in the incidence of CRC. The main reasons are ageing population, increased consumption of processed food, obesity, genetic predispositions. Aim. To review the latest scientific developments and novel factors on the epidemiology, etiology, pathogenesis of colon cancer, focusing on the influence of genetics and epigenetics, risk factors, and the advancement of prevention and treatment methods. Material and methods. The research method is a literature review. Publications were searched in the PubMed database using the following keywords and their combinations in English: colon cancer, colorectal cancer, management, prevalence, causes, risk factors, genetic and epigenetic changes. Selection criteria for publications: scientific articles in English relevant to the research topic and 90% of articles published in the last 10 years (2014–2024). Results. Using theoretical analysis methods, 72 publications were selected that met the inclusion criteria. Our findings emphasize the central role of genetic mutations (particularly in APC, TP53, KRAS and MMR) and epigenetic alterations, such as DNA methylation and histone modification, in the pathogenesis of colorectal cancer. These genetic and epigenetic factors drive the progression from benign polyps to malignant carcinomas, with environmental, lifestyle, and chronic disease factors also playing a critical role. In particular, diet, physical inactivity, smoking and alcohol significantly increase risk, especially in men and those over 50. Innovations such as CRISPR/Cas9 offer new avenues for targeted treatments, while advances in vaccines and liquid biopsy techniques are improving immune response activation and disease monitoring. In addition, diets rich in fiber, antioxidants and healthy fats, as well as the use of probiotics and NSAIDs, are key to reducing cancer risk through their anti-inflammatory effects and promoting gut health. Conclussions. This review highlights the significant impact of genetic and epigenetic factors on colorectal cancer (CRC) development, in addition to the role of lifestyle and environmental exposures. It highlights the potential of CRISPR/Cas9, immunotherapies, and liquid biopsies in pioneering personalized CRC treatments and early detection. Advances in prevention and technology promise a new era of personalized, effective CRC management strategies.
Keywords: colorectal cancer; colon cancer; epigenetic and genetic changes; MMR; Lynch syndrome